2022
DOI: 10.1111/famp.12759
|View full text |Cite
|
Sign up to set email alerts
|

Between cornfields and Kinfolk: Identity management among transgender youth in Midwestern families and communities

Abstract: Transgender and gender diverse (TGD) youth face high rates of discrimination and victimization in their communities and families that contribute to elevated rates of behavioral health concerns. While the individual links between community and family environments and well‐being for this population are clear, how these environments work in unison remains unclear. Furthermore, the methods TGD youth use to manage their identities in these environments are not well understood. We address this gap by exploring the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Presently, the gender-affirmative model of healthcare defines “gender health” as “a child’s opportunity to live in the gender that feels most real or most comfortable to that child” (Hidalgo et al, 2013). While this may be attainable for some trans children, findings from this study problematize the notion that children are tacitly afforded the opportunity to choose which gender feels most real or most comfortable to them and suggest that a multitude of interpersonal and institutional factors influence youths’ abilities to make choices about their genders and health and that the social environment in which youth are situated directly impacts how they manage their identities (Goffnett et al, 2022).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Presently, the gender-affirmative model of healthcare defines “gender health” as “a child’s opportunity to live in the gender that feels most real or most comfortable to that child” (Hidalgo et al, 2013). While this may be attainable for some trans children, findings from this study problematize the notion that children are tacitly afforded the opportunity to choose which gender feels most real or most comfortable to them and suggest that a multitude of interpersonal and institutional factors influence youths’ abilities to make choices about their genders and health and that the social environment in which youth are situated directly impacts how they manage their identities (Goffnett et al, 2022).…”
Section: Discussionmentioning
confidence: 84%
“…With few exceptions, narratives of parental support were rarely constructed in binary terms, and parental refusal of treatment for their children showed up both actively and passively. This suggests that parental acceptance/refusal exists on a spectrum of care and harm and adds to growing research demonstrating that characterizing families of trans youth as either affirming or rejecting is an over-simplification of the family environment (Catapla & McGuire, 2018;Goffnett et al, 2022). A recent qualitative study exploring family support among trans youth, for example, found that while most participants received general support (e.g., housing), gender-specific support was less common (Andrzejewski et al, 2021).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Prior literature found that in addition to disclosure concerns related to being on a parent's insurance posing a barrier to TNB young adults’ access to gender‐affirming healthcare [ 28 ], so too is this a barrier to accessing HIV prevention and testing [ 37 , 38 ]. Options such as free and confidential testing through HIV community‐based organizations (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Michigan has limited protections for lesbian, gay, bisexual, trans and queer (LGBTQ+) people [ 25 ], with lower LGBTQ+ equality than several states [ 26 ]. For example, both a national LGBTQ+ youth survey (23.1% Midwest) [ 27 ] and a qualitative study with Midwestern TNB youth [ 28 , 29 ] identified pervasive interpersonal and structural sexual and anti‐trans stigma and negative impacts on participants’ wellbeing.…”
Section: Introductionmentioning
confidence: 99%